2006
DOI: 10.1074/jbc.m511831200
|View full text |Cite
|
Sign up to set email alerts
|

FRET Analysis of in Vivo Dimerization by RNA-editing Enzymes

Abstract: Members of the ADAR (adenosine deaminase that acts on RNA) enzyme family catalyze the hydrolytic deamination of adenosine to inosine within double-stranded RNAs, a poorly understood process that is critical to mammalian development. We have performed fluorescence resonance energy transfer experiments in mammalian cells transfected with fluorophore-bearing ADAR1 and ADAR2 fusion proteins to investigate the relationship between these proteins. These studies conclusively demonstrate the homodimerization of ADAR1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 42 publications
(42 reference statements)
4
62
1
Order By: Relevance
“…Alternatively, and perhaps most simply, the possibility exists that the heteromeric interactions between p37AUF1 and HuR are weaker than the respective homomeric interactions. In support of this later interpretation is the fact that E d is independent of the concentration(s) of fluors (and thus is likely not an artifact of differential expression), and the fact that FRET efficiency can under certain circumstances be correlated directly with the affinity of protein-protein interaction (Chilibeck et al 2006).…”
Section: Discussionmentioning
confidence: 57%
“…Alternatively, and perhaps most simply, the possibility exists that the heteromeric interactions between p37AUF1 and HuR are weaker than the respective homomeric interactions. In support of this later interpretation is the fact that E d is independent of the concentration(s) of fluors (and thus is likely not an artifact of differential expression), and the fact that FRET efficiency can under certain circumstances be correlated directly with the affinity of protein-protein interaction (Chilibeck et al 2006).…”
Section: Discussionmentioning
confidence: 57%
“…Although several publications by our group and others on the mammalian ADARs point to dimerization that is independent of RNA binding (42,43), other studies in mammalian cells and Drosophila indicate that dsRNA binding is required (40,44). Furthermore, some studies on human ADAR2 suggest that the protein exists only as a monomeric form (32,45).…”
mentioning
confidence: 93%
“…Currently, it is not known whether the interplay between the monomers act cooperatively with respect to their dsRBDs. By use of fluorescence or bioluminescence resonance energy transfer, an examination of ADAR dimerization revealed that the N-terminal dsRBDs are providing much of the interface for the monomer subunits to interact in mammalian cells (43,44).…”
mentioning
confidence: 99%
“…Competition Experiments-ϳ7 ϫ 10 5 HEK 293T cells at 60% confluence were co-transfected with constant amounts of the GluR-B miniB13 (3 g) and of EGFP-ADAR2 (8 g) so that 50% editing of the Gln/Arg site was obtained, and an increasing amount of EGFP-ADAR1 (4,8,16, and 24 g). pEGFP (V-EGFP) was also transfected so that the total concentration of exogenous DNA transfected was equal (total DNA transfected at each experimental point was 35 g).…”
Section: Methodsmentioning
confidence: 99%